Collaboration of Teachers, Parents, and Counselors in Overcoming Non-Academic Problems of Elementary School Students - Darmiany Darmiany; Ida Bagus Kade Gunayasa; Asrin Asrin; Mohammad Archi Maulyda (Jurnal Ilmiah Sekolah Dasar, 2022)
Student problems at school not only include academic problems, but also non-academic problems. One effort to overcome this is by collaborating with teachers, parents, and counselors. This study aims to produce a collaborative model of teachers, parents, and counselors based on experiential learning to solve students' non-academic problems. The research method used is Research and Development (RnD). The research instrument used was a semi-open questionnaire related to students' non-academic problems, a questionnaire on parental understanding, and model validation instruments. The subjects in this study were 8 elementary school teachers and guardians of students who had a tendency to non-academic problems. Analysis of the data used is a test of validity, practicality, and effectiveness. The results of the study show that non-academic behavior that is disturbing and difficult for teachers to overcome is disrespectful and disruptive. Meanwhile, the understanding of parents regarding this issue is still low. To solve this problem, the developed model will have several scenarios, including; concrete experience; reflective observation; abstract conceptualization; active experimentation & evaluation. The results showed that the involvement of parents and counselors greatly influenced efforts to minimize non-academic problems experienced by students. This model will have a direct impact on the ease with which teachers in schools deal with students who have non-academic problems.